Effect of exhaust gas recirculation rate on performance, emission and combustion characteristics of a common-rail diesel engine fuelled with n-butanol–diesel blends. Issue 4 (18th May 2020) - Lamani, Venkatesh Tavareppa; Yadav, Ajay Kumar; Gottekere, Kumar Narayanappa
ABSTRACT: Increasing fears of fossil fuel attenuation and tough emission protocols compel the research community to explore alternative renewable fuels for diesel engines. Butanol is desirable among renewable fuels due to its properties favorable to diesel engines. This study focused on the suitability of exhaust gas recirculation (EGR) and optimum injection timing on the performance, combustion and exhaust emission characteristics of common-rail direct-injection (CRDI) engine fueled with n-butanol-blended diesel using experimental and computational fluid dynamics (CFD) simulation. Various EGR rates and injection timings are considered for different butanol–diesel blends (0, 10, 20 and 30%). Obtained simulation results are validated with experimental data and found to be in good agreement. For all EGR rates and blends, nitrogen oxide (NO) emission is reduced drastically, whereas carbon monoxide (CO) and soot emissions are decreased moderately, with increase in n-butanol–diesel blends. The CO and soot emissions increase with EGR rate due to oxygen deficiency as well. Brake thermal efficiency is reduced by approximately 1% for neat diesel (Bu0) with increase in EGR rates. Soot emission for Bu30 (15 ° Before top dead centre (BTDC) is decreased by 23, 25, 24 and 26% for 0, 10, 20 and 30% EGR rates, respectively, compared to Bu0 (12° BTDC).